Effectiveness of Virtual/Augmented Reality–Based Therapeutic Interventions on Individuals With Autism Spectrum Disorder: A Comprehensive Meta-Analysis - Karami, Behnam; Koushki, Roxana; Arabgol, Fariba; Rahmani, Maryam; Vahabie, Abdol-Hossein (Frontiers in Psychiatry, 2021)
In recent years, the application of Virtual Reality (VR) for therapeutic purposes has escalated dramatically. Favorable properties of VR for engaging patients with autism, in particular, have motivated an enormous body of investigations targeting autism-related disabilities with this technology. This study aims to provide a comprehensive meta-analysis for evaluating the effectiveness of Virtual Reality (VR) on the rehabilitation and training of individuals diagnosed with an autism spectrum disorder. Accordingly, we conducted a systematic search of related databases and after screening for inclusion criteria, reviewed 33 studies for more detailed analysis. Results revealed that individuals undergoing VR training have remarkable improvements with a relatively large effect size with Hedges g of 0.74. Furthermore, the results of the analysis of different skills indicated diverse effectiveness. The strongest effect was observed for daily living skills (g=1.15). This effect was moderate for other skills: g=0.45 for Cognitive skills, g=0.46 for Emotion regulation and recognition skills, and g=0.69 for social and communication skills. Moreover, five studies that had used augmented reality also showed promising efficacy (g=0.92) that calls for more research on this tool. In conclusion, the application of VR-based settings in clinical practice is highly encouraged, though their standardization and customization need more research.